ampG Gene of Pseudomonas aeruginosa and Its Role in β-Lactamase Expression - Zhang, Ying (American Society for Microbiology (ASM), 2010)
In enterobacteria, the ampG gene encodes a transmembrane protein (permease) that transports 1,6-GlcNAc-anhydro-MurNAc and the 1,6-GlcNAc-anhydro-MurNAc peptide from the periplasm to the cytoplasm, which serve as signal molecules for the induction of ampC β-lactamase. The role of AmpG as a transporter is also essential for cell wall recycling. Pseudomonas aeruginosa carries two AmpG homologues, AmpG (PA4393) and AmpGh1 (PA4218), with 45 and 41% amino acid sequence identity, respectively, to Escherichia coli AmpG, while the two homologues share only 19% amino acid identity. In P. aeruginosa strains PAO1 and PAK, inactivation of ampG drastically repressed the intrinsic β-lactam resistance while ampGh1 deletion had little effect on the resistance. Further, deletion of ampG in an ampD-null mutant abolished the high-level β-lactam resistance that is associated with the loss of AmpD activity. The cloned ampG gene is able to complement both the P. aeruginosa and the E. coli ampG mutants, while that of ampGh1 failed to do so, suggesting that PA4393 encodes the only functional AmpG protein in P. aeruginosa. We also demonstrate that the function of AmpG in laboratory strains of P. aeruginosa can effectively be inhibited by carbonyl cyanide m-chlorophenylhydrazone (CCCP), causing an increased sensitivity to β-lactams among laboratory as well as clinical isolates of P. aeruginosa. Our results suggest that inhibition of the AmpG activity is a potential strategy for enhancing the efficacy of β-lactams against P. aeruginosa, which carries inducible chromosomal ampC, especially in AmpC-hyperproducing clinical isolates.